THE LAW OF PRODUCTIVE ZAKAT IN ISLAM AND ITS IMPACT TOWARDS ECONOMY - Anwar (International Journal of Engineering Technologies and Management Research, 2017)
The purpose of zakat is to develop socio-economic value, and it will be hard to be achieved if there is no active role from the organizer (amil) whom is expected to be professional and innovative in organizing the zakat funds. The objective of this research is to know how the zakat productive empowerment in Islamic law perspective. This research used Library Research. The researcher gathered from the books, journals, magazines, and some reports related to the study. Scientific investigation is a form of qualitative research as it pertains to Islamic science that comes from al-Quran and al-Hadith. Generally, there are three instruments known in the data collection, namely observation, interviews and documents study or literature review. This research used only the documents or literature review. Therefore, Data collection methods used to obtain information related to zakat productive in Islamic law perspective is only based on the documentation method. Documentation is inscribed objects that can provide a wide range of information. To meet this method, data is collected based on information obtained from libraries and documents related to the problems of this study. The result of this research is Productive zakat empowerment according to Islamic law is justifiable, as long as pay attention to the basic needs for each mustahiq in the form of consumptive urgent to be addressed immediately.